Elaboración Sostenible de Harina de Chile Jalapeño (Capsicum annuum L.) Mediante Secado Solar Tecnificado - Pech-González, Gustavo Antonio; Ceballos-Falcón, Érika Guadalupe; González-Cortés, Nicolás; Jiménez-Vera, Román (European Scientific Journal, ESJ, 2018)
Jalapeño pepper (Capsicum annuum L.) is a crop in protected natural areas of Tabasco, Mexico. Solar drying is a non-polluting energy that is applicable to food processing. This paper focuses on comparing the microbiological quality of dehydrated jalapeño peppers by means of three methods: direct solar (SD), electric stove (EE), and experimental solar dryer (SSE). SD drying was carried out in zinc sheet by conduction. The drying in EE was at a temperature of 70°C and the SSE has an internal temperature of 43 ° C ± 2 ° C. The dehydrated chiles were crushed in artisanal equipment, and the flour was stored in tightly closed glass containers at room temperature (22-28 ° C). The drying time was lower in the EE (7 h), followed by the SSE (8 h) and the SD (18 h). With EE, the lowest microbial load was obtained and with SD, the highest was obtained. The flour obtained with the SSE presented a concentration of microorganisms within the Mexican norms: total coliforms (25 CFU / g), Staphylococcus aureus (62 CFU / g), and aerobic mesophiles (57 CFU / g). Although the drying time and the microbial load were lower with the EE, the SSE allowed the elaboration of jalapeño pepper flour with the microbiological quality required for human consumption. Technified solar drying is a sustainable alternative for the dehydration of foods in tropical countries.